2022
DOI: 10.1093/asj/sjac316
|View full text |Cite
|
Sign up to set email alerts
|

The British Association of Aesthetic Plastic Surgeons (BAAPS) Gluteal Fat Grafting Safety Review and Recommendations

Abstract: Superficial gluteal lipofilling (SGL) is a fat grafting procedure that is performed to correct a trochanteric depression and buttock deflation. Brazilian Butt Lift (BBL) is gluteal lipofilling procedure traditionally associated with exaggerated appearance and intramuscular fat transfer. The risk of mortality from fat embolism in Brazilian Butt Lift (BBL) was previously reported as being 1:2500. The actual risk was later estimated to be nearer 1:15,000, which is similar to the mortality risk in abdominoplasty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Detailed recommendations for the safety of aesthetic procedures and in particular for the prevention and management of infectious complications, have been issued by national authorities and scientific societies [9 ▪▪ ,32]. Such recommendations were preceded by highly publicized fatalities in patients undergoing cosmetic procedures abroad [32]. Recommendations also raised the issue of insurance, and particularly the need to cover such procedures [32].…”
Section: Challenges In Managing Patients Who Receive Healthcare Abroadmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed recommendations for the safety of aesthetic procedures and in particular for the prevention and management of infectious complications, have been issued by national authorities and scientific societies [9 ▪▪ ,32]. Such recommendations were preceded by highly publicized fatalities in patients undergoing cosmetic procedures abroad [32]. Recommendations also raised the issue of insurance, and particularly the need to cover such procedures [32].…”
Section: Challenges In Managing Patients Who Receive Healthcare Abroadmentioning
confidence: 99%
“…Such recommendations were preceded by highly publicized fatalities in patients undergoing cosmetic procedures abroad [32]. Recommendations also raised the issue of insurance, and particularly the need to cover such procedures [32].…”
Section: Challenges In Managing Patients Who Receive Healthcare Abroadmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reduce the incidence of fatal and nonfatal pulmonary fat embolisms, the American Society of Plastic Surgeons (ASPS) [ 6 , 7 ] and several authors recommend limiting the fat transfer to the subcutaneous plane [ 6 , 8 , 9 ], where fewer and smaller vessels are located [ 6 , 8 , 9 ]. However, a systematic review found it did not reduce the complication rate significantly in comparison to the injection into the intramuscular and subcutaneous planes ( p = 0.059) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%